Studies of CTNNBL1 and FDFT1 variants and measures of obesity: analyses of quantitative traits and case-control studies in 18,014 Danes - Almind Katrine; Lauritzen Torsten; Sandbæk Annelli; Borch-Johnsen Knut; Mogensen Mette; Andreasen Camilla; Hansen Lars; Jørgensen Torben; Pedersen Oluf; Hansen Torben (BMC, 2009)
Abstract Background A genome-wide scan in unrelated US Caucasians identified rs7001819 upstream of farnesyl-diphosphate farnesyltransferase 1 (FDFT1) and multiple variants within catenin (cadherin-associated protein), β-like 1 (CTNNBL1) to associate strongly with body mass index (BMI). The most significantly associating variants within CTNNBL1 including rs6013029 and rs6020846 were additionally confirmed to associate with morbid obesity in a French Caucasian case-control sample. The aim of this study was to investigate the impact of these three variants on obesity, through analyses of obesity-related quantitative traits, and case-control studies in large study samples of Danes. Methods The FDFT1 rs7001819, CTNNBL1 rs6013029 and rs6020846 were genotyped, using TaqMan allelic discrimination, in a combined study sample comprising 18,014 participants ascertained from; the population-based Inter99 cohort (n = 6,514), the ADDITION Denmark screening study cohort (n = 8,662), and a population-based sample (n = 680) and a type 2 diabetic patients group (n = 2,158) from Steno Diabetes Center. Results Both CTNNBL1 variants associated with body weight and height with per allele effect sizes of 1.0 [0.3-0.8] kg and 0.6 [0.2-0.9] cm, respectively, for the rs6020846 G-allele. No association was observed with BMI and waist circumference. In case-control studies neither of the CTNNBL1 variants showed association with overweight, obesity or morbid obesity (rs6013029: Odds Ratio (OR)overweight = 1.02 [0.90-1.16], ORobesity = 1.09 [0.95-1.25], ORmorbidobesity = 1.26 [0.91-1.74]; rs6020846: ORoverweight = 1.05 [0.93-1.18], ORobesity= 1.13 [1.00-1.28], ORmorbidobesity = 1.17 [0.86-1.61]). However, in meta-analyses of the present and the previous study, both the rs6013029 T-allele and the rs6020846 G-allele increased the risk of developing morbid obesity (rs6013029: ORcombined = 1.36 [1.12-1.64], p = 0.002; rs6020846: ORcombined = 1.26 [1.06-1.51], p = 0.01), and obesity (rs6013029: ORcombined = 1.17 [1.04-1.31], p = 0.007; rs6020846: ORcombined = 1.17 [1.05-1.30], p = 0.004). The FDFT1 rs7001819 C-allele showed no association with obesity-related quantitative measures or dichotomous measures of overweight, obesity and morbid obesity. Conclusion CTNNBL1 variants associated with body weight and height, and confer the risk of developing obesity in meta-analyses combining the present and a previous study. FDFT1 rs7001819 showed no association with obesity, neither when analysing quantitative traits nor when performing case-control studies of obesity.